ПСИХОЛОГО—ПЕДАГОГІЧНІ УМОВИ РОЗВИТКУ МОВЛЕННЯ ПЕРШОКЛАСНИКІВ ЗАСОБАМИ МАЛИХ ФОЛЬКЛОРНИХ ЖАНРІВ (Педагогіка вищої та середньої школи, 2006)
The aims of the lessons in the Ukrainian language, which are enlarging and activization of lexicon, forming and developing of the skills o f oral and written spuch, supplying of the mental development of pupils, are defined on the present stouge of the new junior school's development.The most important device of influence on a child is beauty and magnificence, power and expressiveness of native words. Children can understand the dupest colour of words through the words the beauty enters their souls.